Gender Disparities in Inflation during the Cost-of-Living Crisis in Europe: A Novel Decomposition - Denisa Maria Sologon; Karina Doorley; Cathal O'Donoghue (Institute of Labor Economics (IZA), 2024)
This paper evaluates the gender-specific distributional impact of the recent cost-of-living crisis in six European countries using the Household Budget Survey to assess the degree of regressivity (affecting lower income households more) or progessivity (affecting higher income households more) of inflation experienced by households between April 2021 and July 2023. Despite a growing literature on the distributional impact of inflation, there is limited evidence on gender differentials. We innovate by applying distributional measures and a decomposition method adapted from the taxation literature extended with a gender dimension to assess gender differences in inflation regressivity or progressivity, isolate the average inflation rate from the inflation structure effect and identify the drivers of regressivity/progressivity by broad commodity groups (food, heating/electricity, motor fuels, other goods and services). The findings highlight the greater regressive inflation faced by female-headed households compared to men in middle-income countries like Portugal, Poland and Hungary and high-income countries like Ireland. In Germany overall inflation has a neutral impact on women, whereas Finland stands out with a progressive inflation, more pronounced for female-headed households. Consistent across countries, the burden of food and heating/electricity inflation is disproportionately borne by low-income households. Heating/electricity inflation has a larger regressive contribution to overall inflation for female-headed households in all countries, whereas for food this holds only in Poland and Hungary. The findings highlight the need for targeted policies to address potential inequalities arising from differential consumption patterns and protect the most vulnerable groups.
Keywords: D12; D31; E31; I30; J16; 330; regressive inflation; inflation and gender; distributional effect and gender; progressive inflation